PENGARUH MODEL PEMBELAJARAN SENTRA DAN DISIPLIN BELAJAR TERHADAP KEMAMPUAN MATEMATIKA SISWA - Junaedah Na; Sigit Wibowo (Akademika : Jurnal Teknologi Pendidikan, 2016)
This research aims to examine: 1). the difference between the results of the acquisition ofmathematical ability of students who that use of learning centers and the use of classical learning model 2).The influence of the interactions between models of learning and learning discipline against the math skills ofstudents. 3). Difference tallies the results of the mathematical ability of students of high discipline 4). Thedifference in obtaining the results of the math skills of students who have low discipline.This research uses experimental methods, with a 2 x 2 factorial design. The target population is theentire student group B Al-TKIT Izzah in Serang. Samples taken with purposive sampling technique based oncertain characteristics and traits, so that selected 30 students. Data capture techniques are analyzed usingdescriptive analysis and inferential analysis in the form of two lines of ANAVA to test Hypotheses followed byTukey test. Testing statistical requirements covering testing normality with the Kolmogorov-Smirnov test andtesting its homogeneity using Levene test. Results of the study showed that a third of the normal variable dataand homogeneous.The research results showed that: 1). There is a value of a value of α = 0.05 sig then math skillsstudents’ use Learning Center model is superior to 2). There is a value of α = 0.05 sig means that there isinteraction a positive influence between the model of learning centers and learning of classical models with thediscipline of learning math ability against a. 3). There is a value Q calculate > 15.54. Q Table = 8.33 Meansmath skills students use learning centers a disciplined learning high superior to 4). There is a value Qcalculate > 11.18 Q Table =. 8.33 Means math skills students use learning centers that discipline is superiorto the low learning in students with models of classical learning